DETERMINE THE UNIT COST OF SECTION CAESAREA DELIVERY AT KENDANGSARI MERR MOTHER AND CHILD HOSPITAL SURABAYA - Ratnasari, Yuni; Marina, Anna; Desipradani, Gita (SUSTAINABLE, 2023)
ABSTRACT This study aims to determine the unit cost of cesarean section delivery at Kendangsari Merr Mother and Child Hospital Surabaya using the activity-based costing system method. Researchers use a qualitative research approach. The results showed that the calculation of the unit cost of cesarean section delivery can detail several fees of one particular action service by tracing the activity activities that occur during the service process so that it is very minimal if there are unexpected costs that arise for the needs of the action. Keywords:: cesarean section delivery, unit cost